1996
DOI: 10.2307/2963475
|View full text |Cite
|
Sign up to set email alerts
|

Holocene Paleoenvironments of Northeast Iowa

Abstract: This paper presents the biotic, sedimentary, geomorphic, and climatic history of the upper part of the Roberts Creek Basin, northeastern Iowa for the late—glacial and Holocene, and compares these records with a C—O isotopic sequence from Coldwater Cave, 60 km northwest of Roberts Creek. The biotic record (pollen, vascular plant and bryophyte macrofossils, and insects) is preserved in floodplain alluvium that underlies three constructional surfaces separated by low scarps. Each surface is underlain by a litholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 50 publications
0
85
1
Order By: Relevance
“…9). Evidence supporting the reconstruction of boreal conditions is provided by the plentiful macrofossil records of forest shrubs and herbs, aquatic and wetland taxa including bryophytes, and insect remains (Baker et al, 1996). Macrofossils of U. americana (bud scales), Juglans cinerea, T. americana, Ostrya virginica (leaves), F. nigra, Carpinus caroliniana, and Quercus, together with understorey taxa associated with deciduous forest, were recovered from the early Holocene sediments in association with much higher pollen percentages (Fig.…”
Section: The Interpretation Of Thermophilous-tree Pollen In the Lategmentioning
confidence: 99%
See 2 more Smart Citations
“…9). Evidence supporting the reconstruction of boreal conditions is provided by the plentiful macrofossil records of forest shrubs and herbs, aquatic and wetland taxa including bryophytes, and insect remains (Baker et al, 1996). Macrofossils of U. americana (bud scales), Juglans cinerea, T. americana, Ostrya virginica (leaves), F. nigra, Carpinus caroliniana, and Quercus, together with understorey taxa associated with deciduous forest, were recovered from the early Holocene sediments in association with much higher pollen percentages (Fig.…”
Section: The Interpretation Of Thermophilous-tree Pollen In the Lategmentioning
confidence: 99%
“…Other dates for the Picea/Pinus transition, generally taken as the start of the Holocene in the Minnesota area, are all on whole sediment and cover a range 9700-ca 10,500 14 C yr BP. (The dates on wood at Roberts Creek do not date the start of the Holocene (Baker et al, 1996)). The chronological problems are compounded by the existence of radiocarbon plateaux during this time period.…”
Section: The Interpretation Of Thermophilous-tree Pollen In the Lategmentioning
confidence: 99%
See 1 more Smart Citation
“…While browsing by elk and deer, and potentially bison, may have also had an impact on vegetation dynamics (Anderson 2006), fire with a frequent return interval (1-15 years) would have been required to maintain open vegetation types over such large extents (Dickmann andCleland 2002, Nowacki andAbrams 2008). Fire likely was a major determinant of the Driftless Area's HRV for several thousand years; indeed, paleoecological investigations at locations within or near the Driftless Area revealed that oak ecosystems were the dominant during the late Holocene leading up to Euro-American settlement (Davis 1977, Winkler et al 1986, Baker et al 1996, Bogen and Hotchkiss 2007.…”
Section: Historical Range Of Variability and Modern Changesmentioning
confidence: 99%
“…Storm patterns suggest that summer lightning fires were once common throughout central North America (Komarek 1968), and macrofossils of flowering individual plants indicate that tallgrass prairies were repeatedly burned during the growing season at least millenia ago (Baker et al 1996). Emphasis on promotion and study of dominance of C 4 grasses by prescribed dormant-season fire may lead us to overlook the quite different attributes of grasslands left unburned or burned by summer lightning fires (Howe 1994a).…”
Section: Implications Of Summer Firesmentioning
confidence: 99%